(untitled) (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2020)
Problem-based learning (PBL) methods are the standard in modern science education and provide hands-on, interactive learning experiences. Additionally, modern education practices encourage the inclusion of students with learning disabilities in general education classrooms. It is therefore important for science educators to understand the benefits of PBL and strategies for making these activities accessible to all students including those with learning disabilities. PBL methods have positive effects on academic achievement, student engagement and attitudes, classroom environments, self-efficacy, and social skills for both students with learning disabilities and general education students in the science classroom. When the proper supports and scaffolding are provided, students with learning disabilities are able to fully benefit from PBL approaches in the science classroom.